2019
DOI: 10.1016/j.pubrev.2019.101851
|View full text |Cite
|
Sign up to set email alerts
|

The role of empathy in crisis communication: Providing a deeper understanding of how organizational crises and crisis communication affect reputation

Abstract: This study advances our theoretical knowledge of how organizational crises and crisis communication affect reputation. Prior research solely emphasizes the importance of organizational crisis responsibility in this process. Three experiments show that stakeholders' empathy toward the organization provides a second explanation. The first two experiments demonstrate that victim crises not only inflict less reputational damage than preventable crises because stakeholders consider the organization less responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 39 publications
1
50
1
1
Order By: Relevance
“…Contextualizing student–university relationships in the communal realm suggests a particular level of influence for blame and empathy. Recent research has shown that blame and empathy are interconnected in influencing post‐crisis reputation (Schoofs, Claeys, De Waele, & Cauberghe, 2019), but this study shows their influence on post‐crisis relationships as well. Given the mutual orientation, it is likely that blame and empathy would both have considerable influence, as this study's findings suggest.…”
Section: Discussioncontrasting
confidence: 68%
“…Contextualizing student–university relationships in the communal realm suggests a particular level of influence for blame and empathy. Recent research has shown that blame and empathy are interconnected in influencing post‐crisis reputation (Schoofs, Claeys, De Waele, & Cauberghe, 2019), but this study shows their influence on post‐crisis relationships as well. Given the mutual orientation, it is likely that blame and empathy would both have considerable influence, as this study's findings suggest.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, Schoofs et al. (2019) noted the influence of stakeholders’ empathy on organizational crisis communication outcomes, finding that the empathy generated by the apology strategy improves reputation repair more than the denial strategy. Furthermore, Claeys et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, reputation is structural; it projects the corporate identity as a whole, it generates value, and it can be measured objectively [29]. Several authors point out that reputation is one of the main conditions of business leadership [36][37][38][39].…”
Section: Origin and Relevance Of The Concept 'Corporate Reputation' Imentioning
confidence: 99%
“…For this reason, they are very interested to disseminate relevant information in social media and press in order to answer to the decision-making needs for shareholders and stakeholders. When communication and positive information on companies impact on the expectations of managers and stakeholders, their corporate reputation is likely to increase [35,36].…”
Section: Origin and Relevance Of The Concept 'Corporate Reputation' Imentioning
confidence: 99%
See 1 more Smart Citation